Alternatif Sistem Ekonomi Islam Untuk Indonesia yang Lebih Sejahtera - Dian Indah Cahyani; Sumadi Sumadi (ITB AAS INDONESIA Surakarta, 2015)
Economic development in a country or bangasa is the main foundation in order to realize the welfare of society. The economy of a country strong then, the country will be stronger. To this end, the trend of capitalism that has spread throughout the world led to the shifting economic world order. Understand the rich get richer, the poor poorer, unwittingly been entrenched in every society the world. Free competition, monopoly, is a product of capitalism that has a lot of miserable people in the country of Indonesia is no exception. Pancasila Economic System is an economic system that is excavated and built from the values espoused in Indonesian societyEconomics is the knowledge of the events and feelings associated with human efforts as individuals (private), group (family of nations, organizations) in meeting the needs are endless. The economic function is to develop capabilities in the event of economic, analyzing and assessing the economic problems, whether they are individual, society and the national character.Keywords: alternative, the economic system of Islam, prosperous